(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The main activity in the educational system is the process of education and upbringing, which should focus on the harmonious development of a specific subject - the student. In this, it is necessary to establish the relations of innovative approach to the education system, to provide the student with all the necessary knowledge, skills and competences, and to create competencies. Appropriate and productive use of lower, middle and higher level approaches is important in applying the innovative approach to the educational process